Taming the Pseudoelastic Response of Nitinol Using Ion Implantation. (15th March 2023) - Hinojos, Alejandro; Hong, Daniel; Sriram, Hariharan; Feng, Longsheng; Yang, Chao; Wharry, Janelle P.; Gao, Xuesong; Hattar, Khalid; Li, Nan; Schaffer, Jeremy E.; Wang, Yunzhi; Mills, Michael J.; et al.
Abstract: Implantation of Ni50.5 Ti49.5 wire with 30 MeV Ni 6+ ions at doses (< 0.1 DPA) typically smaller than employed in the literature is shown to systematically alter the pseudoelastic response, with extrema in Berkovich nanoindentation load (+50%), hysteresis (−60%), and recoverable displacement (−19%) occurring at ∼ 3.6 μm below the implantation surface. These extraordinary values are attributed to ∼ 10 to 20 nm amorphous clusters that constrain the stress-induced B2-B19′ phase transformation. This is substantiated by phase field simulations of crystalline-amorphous composites and molecular dynamics simulations of crystalline-vacancy cluster composites showing the spatial refinement of martensite caused by nm-scale defects. The results suggest that ion implantation may potentially expand the processing and performance space for NiTi, by creating amorphous defects at smaller length scales than dislocation substructures produced by conventional deformation processing. Graphical abstract: Image, graphical abstract